Molecular regulations of ethylene signaling in plant salt stress responses - Xin Zhang; Jiawei Sun; Chun-Hai Dong (Plant Stress)
Ethylene serves a pivotal function in plant growth, development, and stress responses. Initially received by receptors, ethylene signals the journey to nuclear transcription factors via downstream elements, prompting the expression of relevant genes and engaging in diverse physiological and biochemical processes. Over the preceding decades, the bulk of research efforts concentrated on unraveling the components of ethylene signaling and deciphering their molecular regulations. Remarkably less attention, however, was devoted to scrutinizing the role of ethylene signaling in fostering salt stress tolerance in plants. Crucial questions, such as whether ethylene positively or negatively impacts salt tolerance, remain insufficiently explored. Similarly, the precise role of ethylene signaling in orchestrating the SOS pathway for salt tolerance is not comprehensively understood. Hence, this article seeks to narrow this knowledge gap by exploring the latest breakthroughs in comprehending how ethylene signaling contributes to plants' responses when encountering salt stress. It will explore ethylene synthesis's role, the functions of ethylene signaling components, and the intricate molecular interplay between ethylene signaling and other pathways during salt stress responses. These studies not only deepen our comprehension of ethylene's involvement in salt stress responses but also offer valuable insights for leveraging this knowledge to develop new plant varieties resilient to salt stress.